Implementasi Peraturan Daerah Bali Nomor 47 Tahun 2019 tentang Pengelolaan Sampah Berbasis Sumber dan Dampaknya terhadap Kesadaran Hukum Masyarakat di Desa Baktiseraga - Adi Putra, Komang; Budiarta, I Wayan (Jurnal Media Komunikasi Pendidikan Pancasila dan Kewarganegaraan, 2026)
This study analyzes the implementation of the Regional Regulation on waste management in Baktiseraga Village, Bali, and its impact on the legal awareness of the community. Effective waste management is crucial for environmental cleanliness and public health. The regional regulation is expected to be a strong legal basis for a structured waste management system and increase the legal awareness of the community. Using qualitative methods, this study collected data through direct observation and interviews with village officials. The results of the study are expected to provide a comprehensive picture of the effectiveness of the implementation of the regional regulation, the challenges faced, and their correlation with increasing the legal awareness of the Baktiseraga Village community in waste management. This study will examine in more depth the factors that influence the success of the regulation implementation, including the role of the village government, community participation, and the availability of waste management infrastructure. In addition, this study will also identify obstacles and solutions to increasing legal awareness and active participation of the community in waste management in Baktiseraga Village, as well as recommend strategies for optimizing the implementation of the regional regulation in the future.